Correlation between TICAM1 gene polymorphisms and community‐acquired pneumonia in children. Issue 8 (3rd April 2020) - Yang, Yong; Yang, Suiyu; Chen, Zongbo; Liu, Li
Abstract: This study aims to explore the relationship between single nucleotide polymorphisms (SNPs) of the TICAM1 gene and community‐acquired pneumonia (CAP) in Chinese children. The polymorphisms of eight tag SNP (TagSNP) locus of TICAM1 were detected using the improved multiplex ligation detection reaction (iMLDR) assay in 375 children with CAP (average age, 37.8 ± 21.6 months) and 306 healthy children (average age, 38.5 ± 23.8 months). The correlation between polymorphisms of these TagSNPs and the risk, severity, sepsis, and CRP level of childhood CAP were evaluated using logistic regression analysis. The CC genotype of rs11466711T/C locus of TICAM1 is correlated with childhood CAP susceptibility, which significantly reduced the risk of childhood CAP ( P  < .05), The AA genotype of the rs6510826G/A locus and haplotype CCCA were associated with CRP level in childhood CAP, which significantly increased the risk of CRP increase ( P  < .05 and P  < .01, respectively), The AA genotype of rs35747610G/A site is associated with sepsis in childhood CAP, significantly reduced risk of sepsis ( P  < .05). While the haplotype CCCG of this locus led to a significant reduction in the risks of childhood CAP, severe pneumonia and pneumonia sepsis (all P  < .05). TICAM1 has multiple functional variants closely related to the development and progression of childhood CAP, and these variations may have a synergistic effect on the development of childhood CAP.